The Influence of Parity Against a Percentage of Estrus of Ekor Tipis Sheep that are Synchronized Estrus Using Prostaglandin F2α (PGF2α) - Hasan, F.; Sitepu, S. A. P.; Alwiyah, Alwiyah (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
Obstacles faced in the development of sheep are the lack of sheep going. One of the technologies that can be utilized to increase the population of cattle, sheep is to use artificial insemination, estrus observation on sheep but hard to do, for it needs to be done using the estrus synchronization Prostaglandin F2α. The success of the estrus synchronization program is one of them influenced by parity. The aim of this research was to know the extent of the success rate of the synchronization estrus of thin-tail Sheep range of parity by administering Prostaglandin F2α (PGF2α). The material used on these research Prostaglandin F2α  (PGF2α), a ewe, first child, second child and third child of  thin sail Sheep. Experimental design used in the study was a randomized Complete Design (RAL) non factorial by 4 the treatment and 5 repeated. The treatment given is the wearing of Prostaglandin F2α (PGF2α) Thin-tailed Sheep to a ewe, first child, second child and third child of  Thin Tail Sheep. Parameters observed is the success rate of synchronization of estrus. The results showed that administering prostaglandin F2α (PGF2α) Thin-tailed Sheep to females of different real parity has no effect (P > 0.05) of the success rate of synchronization of estrus. It could be concluded that the thin-tailed sheep of parity which examined did not have an effect on the success of the synchronization of estrus with Prostaglandin F2α uses (PGF2α).